PCR detection of Toxoplasma gondii B1 gene in women suffering from abortion - Mahmood, Aseel S.; Al-Sarray, Sabeeha A.; Al-Kazaz, Abdulkareem (Maǧallat Markaz buhūt al-taqniyyat al-ahyāʼiyyat (Online), 2019)
Background: Primary infection of maternal with toxoplasmosis during gestation and this infection transmission to the fetus continue to be the cause complex disease in offspring. Objective: This study was conducted to test the utility of nested Polymerase Chain Reaction (nPCR) assay to detect recent infections with Toxoplasma in abortive women. Material and methods: Toxoplasma gondii DNA was detected by using B1 gene as a target for amplification which was highly specific for T. gondii and is well conserved among all of the tested strains. Blood from 60 abortive women and 25 apparently healthy pregnant women with no history of abortion (as control group) were taken in this current study. Results: The results revealed that nPCR was positive in 48(80%) subjects and negative in 12(20%), Chi-square- χ2 for patients and control was ( 13.82 , 15.75 ) respectively. Conclusion: It can be concluded that nPCR assay in blood has advantage in detection of recent and active toxoplasmosis.